Physiological performance characteristics of danish national team handball players 1990-2016: Implications on position-specific strength and conditioning training - Bøgild, P.; Jensen, K.; Kvorning, T. (The Journal of Strength and Conditioning Research, 2020)
The aims of this study were: (a) to examine the anthropometric and physiological performance characteristics in male and female national team handball (TH) players before and after 2000; and (b) to compare anthropometry and physiological performance characteristics between court playing positions in male and female national TH players. Using a federal database containing physiological test data from 1990 to 2016 of more than 800 national A and U (under 21 years) TH players, data from 175 men and 138 women were extracted by their first appearance for pre- or post-2000 and sorted by playing positions. The level of significance was set at p < 0.05. Pre- vs. post-2000 male A showed no differences, whereas differences were found in male U, female A, and female U. General position-specific differences for both sexes were wings being lowest, lightest, and having lowest fat-free mass (FFM), pivots having higher body mass and FFM than back-court players, and higher %BF than wings. Back-court players and wings had higher jump and reach (JR) than pivots, and wings were faster on 30 m than pivots. Based on these findings, no general differences seem to exist before and after the year 2000 in the observed physiological parameters. The primary differences between playing positions were anthropometric, whereas the physiological performance characteristics, in general, did not differ between playing positions, except for the pivots' lower JR and the wings' faster 30 m, indicating that earlier documented differences in on-court work demands had not, in general, impacted the players' physiological performance characteristics.